2004
DOI: 10.1093/toxsci/kfh241
|View full text |Cite
|
Sign up to set email alerts
|

No-Observed Effect Levels for Carcinogenicity and for in vivo Mutagenicity of a Genotoxic Carcinogen

Abstract: To elucidate the relationship between in vivo carcinogenic and mutagenic potentials of genotoxic carcinogens, low doses were tested in the livers of Big Blue transgenic rats with 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx). Male Big Blue rats were fed a diet containing 0.001, 0.01, 0.1, 1, 10, or 100 ppm of MeIQx for 16 weeks, and the frequencies of lacI mutants and glutathione S-transferase placental form (GST-P) positive foci in the liver were determined. The mutation frequencies significantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 34 publications
5
45
0
Order By: Relevance
“…Fukushima et al (2003) further suggested that low MeIQx exposure doses lack initiation activity in rat liver. A similar suggestion was also made by Hoshi et al (2004) based on liver GGT+ foci data; they hypothesized that MeIQx lacks direct mutagenicity and thus would exhibit a threshold for carcinogenicity. Recently, Fusushima and associates (Wei et al 2006) also use liver GGT+ foci data to show that a no effect level exists not only for Fisher 344 rats but also for BN rats.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Fukushima et al (2003) further suggested that low MeIQx exposure doses lack initiation activity in rat liver. A similar suggestion was also made by Hoshi et al (2004) based on liver GGT+ foci data; they hypothesized that MeIQx lacks direct mutagenicity and thus would exhibit a threshold for carcinogenicity. Recently, Fusushima and associates (Wei et al 2006) also use liver GGT+ foci data to show that a no effect level exists not only for Fisher 344 rats but also for BN rats.…”
Section: Introductionsupporting
confidence: 52%
“…Recently, Fusushima and associates (Wei et al 2006) also use liver GGT+ foci data to show that a no effect level exists not only for Fisher 344 rats but also for BN rats. The conclusion of a carcinogenic threshold by both Fukushima et al (2002Fukushima et al ( , 2003, Wei et al (2006), and Hoshi et al (2004) was based on the lack of statistical significance between dosed and control groups at all but the two highest exposure levels. While the GGT+ focus is a useful marker for tumor initiation, it is commonly recognized that the absence of statistical significance between control and low dosed groups alone cannot be used to establish a threshold effect for carcinogenicity or initiation activity.…”
Section: Introductionmentioning
confidence: 99%
“…Rats exposed to this carcinogen were examined to determine the formation of 1) MeIQx-DNA adducts [105], 2) mutations at the H-ras locus [106] and in LacI transgenes [107], 3) pre-neoplastic lesions (PNL) in the form of GST-positive foci [105], and 4) hepatocellular adenomas and carcinomas [108]. These endpoints were evaluated at 4, 16, 16-32 and 56 weeks of repeat dosing, respectively.…”
Section: Appendix 1 Analysis Of the Relationships Among Pods For Carmentioning
confidence: 99%
“…However, the prevailing paradigm is that genotoxic carcinogens have no threshold for exerting their potential for tumor induction. Meanwhile, recently, there are increased numbers of reports supporting that low doses of some genotoxic carcinogens showed a practical threshold as in so-called nongenotoxic carcinogens (Tsuda et al, 2003;Hoshi et al, 2004). From the viewpoint of this new paradigm, there is a very low possibility that hepatocellular tumors are induced in the NFLXtreated patients and the consumers ingesting food that is contaminated with NFLX.…”
Section: Discussionmentioning
confidence: 99%